PENGARUH PEMBERDAYAAN APARATUR, PENGAWASAN DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA TANJUNGBALAI - Herna Rahmi; Novida Timoria Siregar; Evi Rahmwati (Manajemen dan Bisnis, 2021)
The formulation of the problem in this study is whether the empowerment of the apparatus, supervision and work environment simultaneously has a positive and significant effect on the work productivity of the employees at Library and Records Office, Kota Tanjungbalai. This study aims to determine the effect of apparatus empowerment, supervision and work environment on the work productivity of the employees at Library and Records Office, Kota Tanjungbalai. The sample in this study were all employees of the Office of Library and Archives of Tanjungbalai City, which numbered 38 people. The data analysis technique in this research is Multiple Linear Regression.The results of this study indicate; Apparatus empowerment partially has a positive and significant effect on employee work productivity; Supervision partially has a positive and significant effect on employee work productivity; The work environment partially has a positive and significant effect on employee work productivity; Empowerment of the apparatus, supervision and work environment simultaneously has a positive and significant effect on employee work productivity.